O cinema de diáspora indiano na Trilogia dos Elementos de Deepa Mehta - Manghirmalani, Juily Jyotsna Seixas (2016)
This research aims to study the films that form the Elements Trilogy, by the Indo-Canadian director Deepa Mehta. Released between 1996 and 2005, the trilogy is part of the production by the Indian diaspora, that is to say, films without strictly defined national borders. Recurring themes in transnational films will be addressed, such as class, ethnicity, sexuality and the concept behind nations. Our purpose is to understand the power structures in India and its implications on female gender policies in these films. The trilogy comprises Fire (1996), 1947-Earth (1998) and Water (2005) and approaches three moments in Indian history throughout the female subjectivity. Deepa Mehta proposes discussions through the criticism presented in her films regarding the interconnection between the fundamentalism Hinduism and women's role in Indian society and culture. We intend to detect these criticisms as we analyze sequences in the three films, using the following method: observation of the narrative pattern, the themes chosen and the articulation of visual and sound strategies.